2015
DOI: 10.1017/s1355617715000053
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Cognitive Difficulties and Cognitive Test Performance as Predictors of Employment Outcomes in People with Multiple Sclerosis

Abstract: Perceived cognitive difficulties and cognitive impairment are important determinants of employment in people with multiple sclerosis (pwMS). However, it is not clear how they are related to adverse work outcomes and whether the relationship is influenced by depressive symptoms. Thus, this study examined perceived and actual general cognitive and prospective memory function, and cognitive appraisal accuracy, in relation to adverse work outcomes. The possible mediating and/or moderating role of depression was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 67 publications
2
48
0
Order By: Relevance
“…Previous work examining cognitive impairment in relation to employment in MS had identified the SDMT to also be one of the main predictors of employment status;6 7 28 the CVLT-II has also predicted reduced employment status in a longitudinal study 7. Although simple strategies may overcome memory deficits, at least when they are mild, the ‘bandwidth’ limitations of reduced information processing speed are less easy to manage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work examining cognitive impairment in relation to employment in MS had identified the SDMT to also be one of the main predictors of employment status;6 7 28 the CVLT-II has also predicted reduced employment status in a longitudinal study 7. Although simple strategies may overcome memory deficits, at least when they are mild, the ‘bandwidth’ limitations of reduced information processing speed are less easy to manage.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the specific cognitive deficits in MS has led to more sensitive patient-reported measures being developed in which relatively close correlation is seen between subjective measures of cognitive impairment and objective outcomes 23. Recent work has also suggested that patient-reported perceptions of cognitive difficulties may be predictive of unemployment status independent of mood and objective memory performance 6. This finding may reflect a relative insensitivity of standard tests to subtle cognitive impairments at a time when ‘subclinical’ cognitive impairment is beginning to cause difficulties with work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We would argue that both perceived and performance-based cognitive measures have clinical significance. For example, Honan et al 26 found that both perceived and performance-based cognitive measures significantly predicted employment outcomes in persons with MS. Also, findings from Pardini et al 27 suggest that the PDQ may serve as a proxy measure of subtle structural damage to the memory network of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cognitive deficits in cancer patients are typically assessed using the standard paper-and-pencil tests or in-person interviews, which are time-consuming and labor intensive for patients who are already fatigued [19, 20]. Further, self- reported (or perceived) cognitive deficits do not always reflect a subject’s performance on neuropsychological (or objective) tasks [21-23]. Therefore, there is a need to develop objective cognitive tests that correspond to subjective cognitive impairments that can be useful for cancer patients.…”
Section: Introductionmentioning
confidence: 99%